Impact of IT identity and data privacy on mobile telemedicine use: A UTAUT perspective - Vaddhano, Nyana; Tulipa, Diyah (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
The purpose of this study is to identify potential determinants of the intention to use mobile telemedicine applications. We gathered a total of 187 responses from smartphone users who expressed interest in utilizing Halodoc mobile telemedicine application. This study analyzed the acquired data using PLS-SEM and employed Importance-Performance Mapping (IPMA) to propose possible managerial enhancements for developers of mobile telemedicine applications. Performance expectancy and facilitating conditions have a substantial impact on users' attitude toward mobile telemedicine applications, according to the findings of the study. Usage intention is not directly influenced by performance expectancy or facilitating conditions. While effort expectancy has no effect on attitude, it has a substantial impact on usage intention. The impact of social influence on attitude and behavioral intention is predominantly positive. Data privacy, in contrast to IT identity, does not have a positive impact on usage intention. In general, a favorable attitude toward the application positively influences the user's intent to use mobile telemedicine applications.